Combination of the novel histone deacetylase inhibitor YCW1 and radiation induces autophagic cell death through the downregulation of BNIP3 in triple-negative breast cancer cells in vitro and in an orthotopic mouse model. Issue 1 (December 2016) - Chiu, Hui-Wen; Yeh, Ya-Ling; Wang, Yi-Ching; Huang, Wei-Jan; Ho, Sheng-Yow; Lin, Pinpin; Wang, Ying-Jan
Abstract Background Triple-negative breast cancer (TNBC) is the most aggressive and invasive of the breast cancer subtypes. TNBC is a challenging disease that lacks targets for treatment. Histone deacetylase inhibitors (HDACi) are a group of targeted anticancer agents that enhance radiosensitivity. Bcl-2/adenovirus E1B 19 kDa protein-interacting protein 3 (BNIP3) is a member of the Bcl-2 subfamily. BNIP3 is not found in normal breast tissue but is up-regulated in breast cancer. In the present study, we investigated the anti-cancer effects of a newly developed HDACi, YCW1, combined with ionizing radiation (IR) in TNBC in vitro and in an orthotopic mouse model. Furthermore, we examined the relationship between autophagy and BNIP3. Methods Trypan blue exclusion was used to investigate the viability of 4 T1 (a mouse TNBC cell line) and MDA-MB-231 cells (a human TNBC cell line) following combined YCW1 and IR treatment. Flow cytometry was used to determine apoptosis and autophagy. The expression levels of BNIP3, endoplasmic reticulum (ER) stress- and autophagic-related proteins were measured using western blot analysis. An orthotopic mouse model was used to investigate the in vivo effects of YCW1 and IR alone and in combination. Tumor volumes were monitored using a bioluminescence-based IVIS Imaging System 200. Results We found that YCW1 significantly enhanced toxicity in 4 T1 cells compared with suberoylanilide hydroxamic acid (SAHA), which was the first HDACi approved by the Food and Drug Administration for clinical use in cancer patients. The combined treatment of YCW1 and IR enhanced cytotoxicity by inducing ER stress and increasing autophagy induction. Additionally, the combined treatment caused autophagic flux and autophagic cell death. Furthermore, the expression level of BNIP3 was significantly decreased in cells following combined treatment. The downregulation of BNIP3 led to a significant increase in autophagy and cytotoxicity. The combined anti-tumor effects of YCW1 and IR were also observed in an orthotopic mouse model; combination therapy resulted in a significant increase in autophagy and decreased tumor tissue expression of BNIP3 in the tumor tissue. Conclusions These data support the possibility of using a combination of HDACi and IR in the treatment of TNBC. Moreover, BNIP3 may be a potential target protein for TNBC treatment.